In vitro evaluation of injectable Tideglusib-loaded hyaluronic acid hydrogels incorporated with Rg1-loaded chitosan microspheres for vital pulp regeneration. (15th February 2022) - Atila, Deniz; Chen, Ching-Yun; Lin, Chun-Pin; Lee, Yuan-Ling; Hasirci, Vasif; Tezcaner, Ayşen; Lin, Feng-Huei
Abstract: Injectable systems receive attention in endodontics due to the complicated and irregular anatomical structure of root canals. Here, injectable Tideglusib (Td)-loaded hyaluronic acid hydrogels (HAH) incorporated with Rg1-loaded chitosan microspheres (CSM) were developed for vital pulp regeneration, providing release of Td and Rg1 to trigger odontoblastic differentiation of human dental pulp stem cells (DPSC) by Td and vascularization of pulp by Rg1. The optimal concentrations were determined as 90 nM and 50 μg/mL for Td and Rg1, and loaded in HA and CSM in HAH, respectively. Odontogenic (COL1A1, ALP, OCN, Axin-2, DSPP, and DMP1) and angiogenic (VEGFA, VEGFR2, and eNOS) differentiation of DPSC cultured in the presence of hydrogels was shown at gene expression level. Our results suggest that our injectable hydrogel formulation has potential to improve strategies for vital pulp regeneration. In vivo evaluations are needed to test the feasibility and potential of these hydrogels for vital pulp regeneration. Graphical abstract: Unlabelled Image